BRAF V600E‐specific immunohistochemistry for the exclusion of Lynch syndrome in MSI‐H colorectal cancer. Issue 7 (25th April 2013) - Capper, David; Voigt, Anita; Bozukova, Gergana; Ahadova, Aysel; Kickingereder, Philipp; von Deimling, Andreas; von Knebel Doeberitz, Magnus; Kloor, Matthias
Abstract : The differentiation between hereditary and sporadic microsatellite‐unstable (MSI‐H) colorectal cancer is a crucial step in Lynch syndrome diagnostics. Within MSI‐H colorectal cancers, the BRAF V600E mutation is strongly associated with sporadic origin. Here, we asked whether BRAF V600E‐specific immunohistochemistry (clone VE1) is helpful in separating sporadic from Lynch syndrome‐associated MSI‐H colorectal cancers. To that end, we performed VE1 immunohistochemistry and BRAF sequencing in a series of 91 MSI‐H colorectal cancer specimens from patients tested for Lynch syndrome. Concordance of VE1 immunohistochemistry and molecular BRAF mutation status was observed in 90 of 91 (98.9%) MSI‐H samples. All 11 tumors classified as BRAF V600E mutation‐positive by Sanger sequencing were immunopositive, and 79 (98.8%) of 80 tumors classified as BRAF wild type showed negative staining. All VE1‐positive tumors were MLH1‐ and PMS2‐negative by immunohistochemistry. None of the tumors from mismatch repair (MMR) gene germline mutation carriers ( n = 28) displayed positive VE1 staining, indicating that BRAF V600E mutation‐specific immunostaining has a low risk of excluding Lynch syndrome patients from germline mutation analysis. In conclusion, implementation of VE1 immunohistochemistry was able to detect BRAF ‐mutated MSI‐H colorectal cancers with a sensitivity of 100% and a specificity of 98.8%. Among MLH1‐negative colorectal cancers, the rate of VE1‐positive lesions was 21%, offering the exclusion of these patients from MMR germline testing. Therefore, we suggest the integration of VE1 immunohistochemistry into the diagnostic panel of Lynch syndrome. Abstract : What's new? Lynch syndrome is one of the most frequent hereditary tumor syndromes. But its hallmark feature, high‐level microsatellite instability (MSI‐H), which is caused by genetic defects in the germline, also occurs in sporadic colorectal cancers, complicating its diagnosis. Here, BRAF V600E mutation‐specific immunohistochemical staining, which targets BRAF mutations found exclusively in sporadic colorectal cancer, is reported to successfully distinguish between hereditary and sporadic MSI‐H‐associated disease. Implementation of the antibody could facilitate diagnosis of the hereditary form while avoiding unnecessary cost‐intensive germline mutation analysis in sporadic cases.